Strategi Relationship Marketing Yang Dilakukan Segmen Government PT Telkom Witel Yogyakarta dalam Mempertahankan Loyalitas Pelanggan - Listy Lukita Sani; Asmai Ishak (Journal of Management and Social Sciences, 2023)
The trust, service and communication that exist between PT Telkom Witel Yogyakarta Government segment and its customers will make this relationship marketing strategy key in efforts to maintain customer loyalty. The purpose of this internship activity is to find out and learn good relationship marketing strategies in maintaining customer loyalty. The research method carried out by the author is a qualitative method, while the data used is primary data and secondary data. The descriptive data analysis technique used in this research is to produce a systematic, realistic and accurate picture of the relationship marketing strategy carried out by PT. Telkom Witel Yogyakarta Government Service segment in retaining customers. Results of interviews and observations of PT's Government Segment Relationship Marketing strategy. Telkom Witel Yogyakarta in Maintaining Customer Loyalty is a strategy of direct sales (direct marketing), customer service, loyalty programs, business visits and maintaining product quality.